A Comparison of Two Pain Scales in the Assessment of Dental Pain in East Delhi Children. (14th February 2012) - Khatri, Amit; Kalra, Namita
Abstract : Pain is the most common symptom of oral diseases. Pain perception in children is highly variable and unreliable due to poor communication. Therefore we designed a study to compare pain measurement techniques, that is, visual analogue scale (VAS) and Wong-Baker faces pain rating scale (WBFPS) among Delhi children aged 3 to 14 years undergoing dental extraction. Method . A cross-sectional study was conducted on 180 patients aged 3 to 14 years who had undergone dental extraction. Children were assessed for their pain sensitivity using visual analogue scale (VAS) and Wong-Baker faces pain rating scale (WBFPS ). Result and Conclusion . Pain threshold tends to decline, and the self-management of pain becomes more effective with increasing age. Genderwise result shows that communication ability of boys and girls is similar in all age groups.